Health education through analogies: preparation of a community for clinical trials of a vaccine against hookworm in an endemic area of Brazil. - Maria Flavia Gazzinelli; Lucas Lobato; Leonardo Matoso; Renato Avila; Rita de Cassia Marques; Ami Shah Brown; Rodrigo Correa-Oliveira; Jeffrey M Bethony; David J Diemert (Public Library of Science (PLoS), 2010)
BACKGROUND: Obtaining informed consent for clinical trials is especially challenging when working in rural, resource-limited areas, where there are often high levels of illiteracy and lack of experience with clinical research. Such an area, a remote field site in the northeastern part of the state of Minas Gerais, Brazil, is currently being prepared for clinical trials of experimental hookworm vaccines. This study was conducted to assess whether special educational tools can be developed to increase the knowledge and comprehension of potential clinical trial participants and thereby enable them to make truly informed decisions to participate in such research. METHODOLOGY/PRINCIPAL FINDINGS: An informational video was produced to explain the work of the research team and the first planned hookworm vaccine trial, using a pedagogical method based on analogies. Seventy-two adults living in a rural community of Minas Gerais were administered a structured questionnaire that assessed their knowledge of hookworm, of research and of the planned hookworm vaccine trial, as well as their attitudes and perceptions about the researchers and participation in future vaccine trials. The questionnaire was administered before being shown the educational video and two months after and the results compared. After viewing the video, significant improvements in knowledge related to hookworm infection and its health impact were observed: using a composite score combining related questions for which correct answers were assigned a value of 1 and incorrect answers a value of 0, participants had a mean score of 0.76 post-video compared to 0.68 pre-video (p = 0.0001). Similar improvements were seen in understanding the purpose of vaccination and the possible adverse effects of an experimental vaccine. Although 100% of participants expressed a positive opinion of the researchers even before viewing the film and over 90% said that they would participate in a hookworm vaccine trial, an increase in the number who expressed fear of being vaccinated with a novel vaccine was seen after viewing the video (51.4% post-video versus 29.2% pre-video). Increases were also seen in the proportion who thought that participation in a vaccine trial would be inconvenient or disrupt their daily activities. CONCLUSIONS/SIGNIFICANCE: Even in rural, resource-limited populations, educational tools can be specially designed that significantly improve understanding and therefore the likelihood of obtaining truly informed consent for participation in clinical research. The observed changes in the knowledge and perceptions of the research participants about hookworm infection and the experimental hookworm vaccine demonstrate that the video intervention was successful in increasing understanding and that the subjects acquired knowledge pertinent to the planned research.